Analisis Kodifikasi Diagnosis ICD-10 pada Karakter Keempat terhadap 10 Penyakit Terbanyak di Klinik Brimob Polda Kalimantan Selatan - soraya soraya; Atas Asih Atas Asih; A. Rasyid Ridha R; Muhammad Heriyadi; Nadira Amelia Oktiana (Health Media, 2026)
Accuracy in diagnosis codification based on ICD-10 is an important aspect in improving the quality of morbidity data and supporting healthcare services. The use of the fourth character in ICD-10 plays a role in providing more specific diagnostic information. In practice, inaccurate coding can reduce the validity of medical record data and affect health reporting systems. This study aimed to analyze the accuracy of ICD-10 diagnosis codification on the fourth character for the 10 most common diseases at Brimob Polda South Kalimantan Clinic. The research used a descriptive quantitative method through medical record audits of inpatient data. Data collection focused on identifying the 10 most common diseases and evaluating the conformity between medical diagnoses and ICD-10 codes assigned by health officers. The results showed that the most dominant diseases were Z00 (general examination), J00 (acute nasopharyngitis), and K04.1 (necrosis of pulp). Several diagnoses still used unspecified fourth-character codes such as J02.9 and R50.9, indicating limitations in coding specificity. The study concluded that although disease distribution had been documented properly, the accuracy of fourth-character ICD-10 coding still requires improvement to support more accurate and specific health information systems